Pogue's war : diaries of a WWII combat historian - Pogue, Forrest C. (Lexington, Ky. : University Press of Kentucky, 2001)
"With a foreword by Stephen Ambrose and a preface by Franklin D. Anderson Forrest Pogue (1912-1996) was undoubtedly one of the greatest World War II combat historians. Born and educated in Kentucky, he is perhaps best known for his definitive four-volume biography of General George C. Marshall. But, as Pogue's War makes clear, he was also a pioneer in the development of oral history in the twentieth century, as well as an impressive interviewer with an ability to relate to people at all levels, from the private in the trenches to the general carrying four stars. Pogue's War is drawn from Forr
London in the spring of 1944 -- We learn top secrets or we are bigoted -- Waiting in Cornwall -- Crossing the Channel one day late -- The Lieutenant John Spaulding interview -- First days in the field -- First interviews in the field -- The last weeks of June -- Writing history for a change -- The breakout at Saint-Lô -- Restless days at the rear -- Liberated Paris -- Last Days in Normandy -- Watching Paris come to life -- Opinion and politics in liberated Paris -- Return to the field -- The deadly forest -- The North flank of the bulge -- Regaining lost ground -- Battle for the dam -- The close-up to the Rhine -- Chasing the armor across Germany -- Another form of German culture: Buchenwald -- A non-sober history of the meeting with the Russians -- Pilzen on VE-Day.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Includes index.
English.
Keywords: Pogue, Forrest C. -- Diaries; Pogue, Forrest C; Pogue, Forrest C; Military historians -- United States -- Diaries; World War, 1939-1945 -- Campaigns -- Western Front; World War, 1939-1945 -- Personal narratives, American; Guerre mondiale, 1939-1945 -- Campagnes et batailles -- Front occidental; BIOGRAPHY & AUTOBIOGRAPHY -- Historical; HISTORY -- Military -- World War II; HISTORY -- Military -- Veterans; Military campaigns; Military historians; United States; Western Front (World War (1939-1945)); Tweede Wereldoorlog; Krijgsgeschiedenis (wetenschap); Guerre mondiale (1939-1945) -- Campagnes et batailles -- Front occidental -- Récits personnels américains.; Soldat; Weltkrieg; Erlebnisbericht; USA; 1939 - 1945; diaries; autobiographies (literary works); Personal narratives; Autobiographies; Diaries; Personal narratives -- American; Autobiographies; Diaries; Personal narratives; Autobiographies; Journaux intimes; Récits personnels